Amide Proton Transfer-Weighted (APTw) Imaging of Intracranial Infection in Children: Initial Experience and Comparison with Gadolinium-Enhanced T1-Weighted Imaging. (18th May 2020) - Zhang, Hong; Tang, Xiaolu; Lv, Yanqiu; Hu, Di; Sun, Jihang; Wang, Yan; Zhou, Jinyuan; Peng, Yun
Abstract : Purpose . To evaluate the performance of amide proton transfer-weighted (APTw) imaging against the reference standard of gadolinium-enhanced T1-weighted imaging (Gd-T1w) in children with intracranial infection. Materials and Methods . Twenty-eight pediatric patients (15 males and 13 females; age range 1-163 months) with intracranial infection were recruited in this study. 2D APTw imaging and conventional MR sequences were conducted using a 3 T MRI scanner. Kappa (κ ) statistics and the McNemar test were performed to determine whether the hyperintensity on APTw was related to the enhancement on Gd-T1w. The sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) of APTw imaging to predict lesion enhancement were calculated. Result . In twelve patients with brain abscesses, the enhancing rim of the abscesses on the Gd-T1w images was consistently hyperintense on the APTw images. In eight patients with viral encephalitis, three showed slight spotted gadolinium enhancement, while the APTw image also showed a slight spotted high signal. Five of these patients showed no enhancement on Gd-T1w and isointensity on the APTw image. In eleven patients with meningitis, increased APTw signal intensities were clearly visible in gadolinium-enhancing meninges. Sixty infectious lesions (71%) showed enhancement on Gd-T1w images. The sensitivity and specificity of APTw were 93.3% (56/60) and 91.7% (22/24). APTw demonstrated excellent agreement (κ = 0.83 ) with Gd-T1w, with no significant difference (P = 0.69 ) in detection of infectious lesions. Conclusions . These initial data show that APTw MRI is a noninvasive technique for the detection and characterization of intracranial infectious lesions. APTw MRI enabled similar detection of infectious lesions to Gd-T1w and may provide an injection-free means of evaluation of intracranial infection.